Angolatitan adamastor, a new sauropod dinosaur and the first record from Angola - Mateus,Octávio (2011)
A forelimb of a new sauropod dinosaur (Angolatitan adamastor n. gen. et sp.) from the Late Turonian of Iembe (Bengo Province) represents the first dinosaur discovery in Angola, and is one of the few occurrences of sauropod dinosaurs in sub-Saharan Africa collected with good chronological controls. The marginal marine sediments yielding the specimen are reported to be late Turonian in age and, thus it represents a non-titanosaurian sauropod in sub-Saharan Africa at a time taken to be dominated by titanosaurian forms. Moreover, Angolatitan adamastor is the only basal Somphospondyli known in the Late Cretaceous which implies in the existence of relict forms in Africa.